2017
DOI: 10.1053/j.ajkd.2016.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Receipt of Intensive Procedures at the End of Life Among Patients Treated With Maintenance Dialysis

Abstract: Background Many dialysis patients receive intensive procedures intended to prolong life at the very end of life. However, little is known about trends over time in use of these procedures. We describe temporal trends in receipt of inpatient intensive procedures during the last six months of life among patients treated with maintenance dialysis. Study Design Mortality follow-back study. Setting & Participants 649,607 adult Medicare beneficiaries on maintenance dialysis who died in 2000–2012. Predictors Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Unexpected critical events are almost certainly related to the emergent presentation needed to secure treatment with hemodialysis for these patients (e.g., high potassium leading to cardiac death). Our findings are consistent with our prior research exploring the palliative needs of Latinos on hemodialysis (3) and national data documenting intensive patterns of end-of-life care among Latino patients on dialysis (4). How best to foster end-of-life planning for undocumented patients with ESKD receiving EOHD exposes the fundamental contradictions inherent in current approaches to caring for these patients.…”
supporting
confidence: 88%
“…Unexpected critical events are almost certainly related to the emergent presentation needed to secure treatment with hemodialysis for these patients (e.g., high potassium leading to cardiac death). Our findings are consistent with our prior research exploring the palliative needs of Latinos on hemodialysis (3) and national data documenting intensive patterns of end-of-life care among Latino patients on dialysis (4). How best to foster end-of-life planning for undocumented patients with ESKD receiving EOHD exposes the fundamental contradictions inherent in current approaches to caring for these patients.…”
supporting
confidence: 88%
“…For example, one study reported that Hispanic patients on dialysis were more likely to undergo intensive medical procedures such as ventilation, tracheostomy, feeding enterostomy, and cardiopulmonary resuscitation in the last 6 months of life. 20 Other studies comparing black to white patients showed that in-hospital death, dialysis discontinuation, and hospice referral differed substantially between the two racial populations examined, as well as across regions of the United States. [21][22][23] Our study differs from these informative studies in a number of ways.…”
Section: Discussionmentioning
confidence: 96%
“…In a survey of patients with CKD in Canada, 36% preferred to die at home or in an inpatient hospice (29%) rather than in a hospital (27%) (10). This contrasts starkly with the current reality of end-of-life care for patients on dialysis, which is more aggressive than that for other life-limiting diseases (5,11,12).…”
Section: Introductionmentioning
confidence: 99%